Formation of the Management System of the Mechanism for Implementing Energy Service Contracts in the Republic of Sakha (Yakutia) - Kladkina, S N; Nogovitsyn, R R (KnE Social Sciences, 2019)
The article is devoted to the actual problem of the northern regions of Russia, which have an extreme climate for life in their territory with a long period of negative temperatures during the year. The mechanism of public-private partnership is of particular relevance in the conditions of budgetary deficit, acting as an effective tool for attracting innovative energy-saving technologies to the housing and utilities sector, which allows achieving substantial financial savings, regardless of the number of energy consumers. Due to the fact that the Northern regions of Russia are characterized by low population density and a small number of energy consumers. The article reveals a system of principles, the observance of which, when implementing the energy saving policy of the Republic of Sakha (Yakutia), will make it possible to increase the effectiveness of its goals of achieving it. The perspective benefit and interest of the parties is presented at interaction within the limits of state - private partnership of both parties of the state and business, at realization of energy service activity. An element of the scientific novelty of our research is the proposal of the management system of the mechanism for implementing energy service contracts for regions with climatic development limitations, with full consideration of the indicated principles of the region’s energy-saving policy, which allows taking into account the specifics of the energy zones available in the territory and the application of a differentiated approach. Keywords: energy saving policy; energy saving; energy efficiency; energy service contracts; management system.